RETINAL ANGIOMATOUS PROLIFERATION: A Quantitative Analysis of the Fundoscopic Features of the Fellow Eye - Marques, JP (2015)
PURPOSE: To quantitatively analyze and compare the fundoscopic features between fellow eyes of retinal angiomatous proliferation and typical exudative age-related macular degeneration and to identify possible predictors of neovascularization. METHODS: Retrospective case-control study. Seventy-nine fellow eyes of unilateral retinal angiomatous proliferation (n = 40) and typical exudative age-related macular degeneration (n = 39) were included. Fundoscopic features of the fellow eyes were assessed using digital color fundus photographs taken at the time of diagnosis of neovascularization in the first affected eye. Grading was performed by two independent graders using RetmarkerAMD, a computer-assisted grading software based on the International Classification and Grading System for age-related macular degeneration. RESULTS: Baseline total number and area (square micrometers) of drusen in the central 1,000, 3,000, and 6,000 μm were considerably inferior in the fellow eyes of retinal angiomatous proliferation, with statistically significant differences (P < 0.05) observed in virtually every location (1,000, 3,000, and 6,000 μm). A soft drusen (≥125 μm) area >510,196 μm2 in the central 6,000 μm was associated with an increased risk of neovascularization (hazard ratio, 4.35; 95% confidence interval [1.56-12.15]; P = 0.005). CONCLUSION: Baseline fundoscopic features of the fellow eye differ significantly between retinal angiomatous proliferation and typical exudative age-related macular degeneration. A large area (>510,196 μm2) of soft drusen in the central 6,000 μm confers a significantly higher risk of neovascularization and should be considered as a phenotypic risk factor.